Dynamics of T cell responses in HIV infection. - Appay, V; Papagno, L; Spina, C; Hansasuta, P; King, A; Jones, L; Ogg, G; Little, S; Mcmichael, A; Richman, D; Rowland-Jones, S (2002)
Cytotoxic CD8(+) T cells play a major role in the immune response against viruses. However, the dynamics of CD8(+) T cell responses during the course of a human infection are not well understood. Using tetrameric complexes in combination with a range of intracellular and extracellular markers, we present a detailed analysis of the changes in activation and differentiation undergone by Ag-specific CD8(+) T cells, in relation to Ag-specific CD4(+) T cell responses, in the context of a human infection: HIV-1. During primary HIV-1 infection, the initial population of HIV-specific CD8(+) T cells is highly activated and prone to apoptosis. The Ag-specific cells differentiate rapidly from naive to cells at a perforin low intermediate stage of differentiation, later forming a stable pool of resting cells as viral load decreases during chronic infection. These observations have significant implications for our understanding of T cell responses in human viral infections in general and indicate that the definition of effector and memory subsets in humans may need revision.